EDUCATION MANAGEMENT AND TEACHER PERFORMANCE IN SECONDARY EDUCATIONAL INSTITUTIONS IN THE URBAN AREA OF THE DISTRICT LEVEL YARINACOCHA, UCAYALI, 2013 - Calixto Arias, Elizabeth Norma (2019)
To develop the research work has been raised,the question What is the relationship betweeneducational management and teacher performancein educational institutions of the secondary levelurban area of the district of Yarinacocha, Ucayali,2013?, for this purpose it was aimed at researchTo determine the relationship between educationalmanagement and teacher performance in educationalinstitutions of the secondary level urban area ofthe district of Yarinacocha, Ucayali, 2013, the typeof study was non-experimental and applied, studydesign was correlational, for which a sample wasselected of size 113 of a population of 208 teachersof secondary level educational institutions, to whom aquestionnaire was applied, consisting of 30 items onthe variable Educational management and 20 itemson the variable Teacher performance, concludingthat there is a significant direct relationshipbetween management Educational and TeachingPerformance.